Magnetic Resonance in Food Science : an Exciting Future. - Renou, J-P; Belton, P. S.; Webb, G. A. (Royal Society of Chemistry, The, Ingram Publisher Services [distributor], 2011)
Annotation The Clermont-Ferrand-Theix Institut National de la Recherche Agronomique (INRA) was proud to organize the 10th International Conference on the applications of Magnetic Resonance in Food Science to celebrate its 10th anniversary. This scientific event was held from 13 to 15 September 2010 in Clermont-Ferrand. The conference attracted 90 participants from 14 countries from all over the world. The conference included 7 invited lectures, 19 oral presentations and 27 oral poster presentations. Moreover, before the scientific sessions, two postgraduate sessions were given in parallel every morning. The conference was divided in 6 sessions covering i) Data processing, ii)New developments/food system, iii) New developments/NMR, iv) Nutrition, v) Metabolomic and vi) Imaging. The book follows the form of the conference. This year's meeting corresponded to its 10th anniversary. The first international conference was held in 1992 at the University of Surrey in Guilford on Professor Peter Belton's and Professor Graham Webb's initiative. During the last 20 years, a lot of developments were performed and the next 20 years are also very exciting. This meeting presentations were focused on the new developments in NMR techniques : hardware as well software with metabolomic and imaging without the new applications of NMR tools in food of course and now in nutrition.
Keywords: Food -- Composition -- Research -- Congresses.; Magnetic resonance imaging -- Congresses.; elektronické knihy; electronic books